2015
DOI: 10.24176/jkg.v1i1.257
|View full text |Cite
|
Sign up to set email alerts
|

Layanan Informasi Karir Membantu Peserta Didik Dalam Meningkatkan Pemahaman Karir

Abstract: Peserta didik akan selalu dihadapkan dengan sejumlah alternatif,baik yang berhubungan kehidupan pribadi, sosial, belajarmaupun kariernya. Mereka sering mengalami kesulitan untukmengambil keputusan dalam menentukan alternatif mana yangharus dipilih. Salah satunya adalah kesulitan dalam memahamidiri yang berkaitan dengan karirnya dan pengambilan keputusanyang berhubungan dengan rencana-rencana karier yang akandipilih untuk masa depannya. Kesulitan-kesulitan untukmengambil keputusan karier dapat dihindari ketika … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
3
0
4
Order By: Relevance
“…A career information service is a means of delivering information that helps students determining the type of work and meeting the criteria so that the selected job is aligned with their potentials (Pustika, 2019). The role of counseling teacher in helping students to plan their careers according to their abilities, talents and interests is very important because entering a work world, some students might not have not been able to understand the workfield's development, and based on this information, someone might be able to test their compatibility with their individual concepts (Wijaya et al, 2019) This is similar to the opinion by Hidayati (2015) that providing a career information service requires the teacher's creativity to help the students overcoming their problems. The results of research conducted by Dahlan (2015) which revealed that using pictorial media in career information services was effective, as proven by comparing the students' understanding of advanced study before and after being given the services Next, a research conducted by Hartinah, Wibowo, & Tadjri (2015) argued that a life skill-based career information service can effectively improve students' understanding of career planning.…”
Section: Introductionmentioning
confidence: 73%
“…A career information service is a means of delivering information that helps students determining the type of work and meeting the criteria so that the selected job is aligned with their potentials (Pustika, 2019). The role of counseling teacher in helping students to plan their careers according to their abilities, talents and interests is very important because entering a work world, some students might not have not been able to understand the workfield's development, and based on this information, someone might be able to test their compatibility with their individual concepts (Wijaya et al, 2019) This is similar to the opinion by Hidayati (2015) that providing a career information service requires the teacher's creativity to help the students overcoming their problems. The results of research conducted by Dahlan (2015) which revealed that using pictorial media in career information services was effective, as proven by comparing the students' understanding of advanced study before and after being given the services Next, a research conducted by Hartinah, Wibowo, & Tadjri (2015) argued that a life skill-based career information service can effectively improve students' understanding of career planning.…”
Section: Introductionmentioning
confidence: 73%
“…Pemilihan karir sesuai dengan minat jurusan menjadikan siswa termotivasi dalam belajar, tertarik untuk menelusuri jurusan yang dipilih dengan mencari informasi diberbagai sumber, seperti media modul atau buku, melalui komunikasi, media elektronik dan media lainnya. Prayitno (2016), dengan minat jurusan membuat individu dapat dengan konsisten dalam mengambil keputusan karir kedepan. Layanan informasi karir sangatlah penting dan berpengaruh dalam mengambil keputusan karir yang tepat karena layanan informasi dapat dikatan sangat penting dan dibutuhkan dalam segi kehidupan termasuk pada pemberian layanan informasi disekolah.…”
Section: Pendahuluanunclassified
“…Hidayati [15] argues that students are always faced with several alternatives, both related to personal, social, learning, and career life. Therefore, students need to get guidance and assistance to gain an adequate understanding of their various conditions and characteristics, both about their talents, interests, ideas, and various strengths and weaknesses that exist in them.…”
Section: B Analysis Of the General Condition Of Self-verification In ...mentioning
confidence: 99%